Engineered Extracellular Vesicle‐Delivered CRISPR/CasRx as a Novel RNA Editing Tool. Issue 10 (2nd February 2023) - Li, Tianwen; Zhang, Liansheng; Lu, Tao; Zhu, Tongming; Feng, Canbin; Gao, Ni; Liu, Fei; Yu, Jingyu; Chen, Kezhu; Zhong, Junjie; Tang, Qisheng; Zhang, Quan; et al.
Abstract: Engineered extracellular vesicles (EVs) are considered excellent delivery vehicles for a variety of therapeutic agents, including nucleic acids, proteins, drugs, and nanomaterials. Recently, several studies have indicated that clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated 9 (Cas9) delivered by EVs enable efficient DNA editing. However, an RNA editing tool delivered by EVs is still unavailable. Here, a signal peptide‐optimized and EVs‐delivered guide RNA (gRNA) and CRISPR/CasRx (Cas13d) system capable of rapidly inhibiting the expression of targeted genes with quick catabolism after performing their functions is developed. EVs with CRISPR/CasRx and tandem gRNAs targeting pivotal cytokines are further packed whose levels increase substantially over the course of acute inflammatory diseases and find that these engineered EVs inhibit macrophage activation in vitro. More importantly, this system attenuates lipopolysaccharide (LPS)‐triggered acute lung injury and sepsis in the acute phase, mitigating organ damage and improving the prognosis in vivo. In summary, a potent tool is provided for short‐acting RNA editing, which could be a powerful therapeutic platform for the treatment of acute diseases. Abstract : In this study, a signal peptide‐optimized and extracellular vesicles‐delivered CRISPR/CasRx and guide RNA system is developed, capable of rapidly inhibiting the expression of multiple inflammatory cytokines with quick catabolism after performing their functions both in vitro and in vivo, providing a short‐acting RNA editing tool for the treatment of acute inflammatory diseases.